Leading Change and Restructuring the Manitoba Library Association - Stefanko, Alix-Rae (Partnership, 2020)
Provincial and regional library associations provide the infrastructure for effective library advocacy, professional learning, development and networking, and help to lead libraries forward. This article highlights the re-structuring of the Manitoba Library Association, a project initiated to maximize the effectiveness and efficiency of the organization.